Autonomic nervous system and mediating role of respiratory function in patients with ALS - Nieves de Bernardo; José Enrique de la Rubia Ortí; Carlos Villarón-Casales; Jesús Privado; Rosa Maset-Roig; Montse Cañabate; David Sancho-Cantus; Inmaculada Orrit Sanz; Raquel Fernández Fernández; Belén Proaño; Asta Tvarijonaviciute; Camila Peres Rubio; et al. (Scientific Reports)
Abstract Patients with Amyotrophic Lateral Sclerosis (ALS) exhibit altered patterns of respiratory rate and heart rhythm that are directly related to autonomic nervous system (ANS) activity. This study aimed to analyze the role of the ANS in respiratory function, cognition, functionality, and antioxidant capacity in patients with ALS through a predictive model that assesses the mediating activity of respiration. This quantitative, observational, analytical, and cross-sectional clinical study was conducted using a sample of 75 patients diagnosed with ALS. ANS activity, respiratory function, cognition, functionality, and antioxidant capacity were also measured. Using these values, a structural equation model was developed using AMOS V.23 software. The mediational predictive model showed that increased sympathetic nervous system (SNS) activity, in turn, increased respiratory function, whereas the role of the parasympathetic nervous system in respiration was very weak and had the opposite effect. Furthermore, SNS activity increased respiratory function values, which, in turn, improved functional capacity, cognition, and antioxidant power in patients with ALS, with respiratory function playing a mediating role. The mediating effect of respiratory function was observed primarily between ANS and functional disability. For oxidative stress, respiratory function showed a high mediating effect, such that greater respiratory function corresponded to greater antioxidant capacity. Additionally, for cognitive activity, a moderate direct effect of the ANS was observed; however, it was greatly enhanced by respiratory disability. Finally, differences were only found based on sex, with respiratory capacity and antioxidant power being higher in men.